Certain subclasses of analytic functions associated with fractional q-calculus operators - Purohit, Sunil Dutt; Raina, Ravinder Krishna (Mathematica Scandinavica, 2011)
We first define the q-analogue operators of fractional calculus which are then used in defining certain classes of functions analytic in the open disk. The results investigated for these classes of functions include the coefficient inequalities and some distortion theorems. The results provide extensions of various known results in the q-theory of analytic functions. Special cases of our results are pointed out briefly.